Peran Amil dalam Mendukung Pemberdayaan Mustahik pada Program Cahaya Zakat di BAZNAS Kota Tangerang Selatan - Muhammad Ilham Fudholi; Ananda Rizki Amellia; Ni mah Fajriatul Nabila; Muhammad Rusydi Azmi; Echa Rysni Mahalani; Tantan Hermansah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Zakat in contemporary social development is no longer viewed merely as a personal religious obligation, but as a social instrument with significant potential to reduce poverty and enhance community welfare. This study aims to analyze the role of amil in supporting mustahik empowerment through the Cahaya Zakat Program implemented by BAZNAS Kota Tangerang Selatan. Using a qualitative descriptive approach, data were collected through observation, interviews, and document analysis involving amil and internal stakeholders. The findings reveal that amil play a multidimensional role, encompassing not only administrative and technical functions but also social, educational, and facilitative roles. Amil are actively involved in zakat collection, public education, beneficiary verification, and connecting mustahik with sustainable empowerment programs. The study also identifies challenges related to limited human resources during the Ramadan period. Overall, the Cahaya Zakat Program functions not only as a fundraising initiative but also as a medium for strengthening zakat literacy and initiating mustahik empowerment. Strengthening amil capacity and institutional support is essential to enhance the sustainability of zakat-based empowerment